TECHNOLOGY ACCEPTANCE MODEL DALAM PENGGUNAAN FINANCIAL TECHNOLOGY LENDING PADA GENERASI MILENIAL - Maharseni, Ni Wayan Radha; Rasmini, Ni Ketut; Ariyanto, Dodik; Mimba, Ni Putu Sri Harta (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.05.TAHUN.2022, 2022)
This study aims to analyze the factors that influence the actual use of fintech lending in the millennial generation in Central Kalimantan. Fintech lending is a financial service to provides convenience to borrowers by using technology and the internet. The population in this study were all fintech lending users in Central Kalimantan who were registered with the OJK, with a total sample of 400 respondents who were determined based on purposive sampling. The type of data used is primary data collected through the distribution of questionnaires using a 4-point Likert scale. The data analysis technique used is the Partial Least Square (PLS) approach. The results showed that perceived usefulness, perceived ease of use, social influence, and habits had a positive and significant effect on the actual use of fintech lending. On the other hand, perceptions of risk, confidentiality, and trust have no significant effect on the actual use of fintech lending. Researchers suggest for fintech lending service providers continue to update facilities and reduce technological complexity to make it easier to use. The service provider also improves system security to be able to prevent the risk of crime. For further researchers, it is recommended to consider using models other than TAM because there are many models for the acceptance and use of information technology.